Predictors of Positivity Yield among Index Contacts in Harare and Matabeleland South Provinces, Zimbabwe, 2022 - Hamufare Dumisani Mugauri; Owen Mugurungi; Ishmael Chikondowa; Joconiah Chirenda; Kudakwashe Takarinda; Mufuta Tshimanga (Journal of Epidemiology and Public Health, 2023)
Background: Zimbabwe’s Index Testing programme has failed to achieve targets since its inception in 2017. We determined the index testing implementation modalities to identify and recommend effective contact elicitation, tracking and testing modalities to enhance positivity yield.Subjects dan Method: This study conducted a cross-sectional study on 50 multistage selected health facilities. Dependent variables were all clients, (≥15 years) diagnosed with HIV in 2021, whilst independent variables were contact tracking. The study instrument of variable measure was cascade analysis to identify tracing modalities against yield. Quantitative data were summarized as proportions, odds ratios, and adjusted odds ratios at a 5% significance level.Results: Of 6,308 index cases identified, females constituted 53.9% (n=3,401 and 67.6% (n=4,265) were retests. Index testing was offered to 66.4% (n=4,190), accepted by 93.1% (n=3,899) and the elicitation rate was 1:1.3 (n=5,080). A positivity yield of 27.5% (n=1,736) was achieved from 78.6% (n= 3,991) contacts. Mixed method tracking yielded 46.7% (n=349) positivity from a testing rate of 99.5% (n=748) in an urban setup, with 41.4% (n=1,243) preferring health worker referrals. As high as 202 contacts were not tested following elicitation through client referrals. In a rural setup, client referrals accounted for 53.1%, (n=1,103) yet 122 of these were not tested. The highest positivity yield was obtained from health worker referrals at 65.6% (n=196). Being male (aOR=3.09; 95%CI= 2.74 to 3.49), first tester (aOR=1.65; 95%CI= 1.43 to 1.91), anonymous tracking (aOR=8.46; 95%CI:3.37 to 22.75) and testing contacts within 7 days of elicitation (aOR=2.78; 95%CI=2.44 to 3.18) were identified as high predictors of positivity yield among index contacts.Conclusion: The identified high positivity yield among men, first-time testers and contacts tested within 7 days of elicitation may inform index testing focussing to improve program performance. Implementation fidelity and differentiated contact referrals were recommended to mitigate attritions at each stage of the index cascade to yield the best results on index contact tracing and testing. Keywords: targeted testing, HIV testing services, index contact tracing and testing, index testing cascade Correspondence:Hamufare Dumisani Mugauri. Faculty of Medicine and Health Sciences, Department of Primary Healthcare Sciences, New Health Sciences Building, Parirenyatwa Complex, Mazowe Road, Harare, Zimbabwe. Email: dumiwaboka@gmail.com. Mobile: +263772314894.